Self-Control and Self-Regulated Learning on Students - Dita Praweswari; Nur’aeni Nur’aeni (Proceedings Series on Social Sciences & Humanities, 2021)
Students who are active in non-academic activities can get different academic scores from students who do not participate in student organizations. This study examines the relationship between self-control and self-regulated learning of students who are members of the Student Organization of the University of Muhammadiyah Purwokerto-Indonesia. This study uses quantitative methods. The sample of this research is 88 students who follow the Student Organization. Sample selection using probability sampling technique by taking 14% of the total population. Data were collected using an online questionnaire, and namely, google Forms. The instrument used is a scale of self-control and self-regulated learning. The data analysis technique uses the product-moment method from Karl Pearson. This study indicates a positive and significant relationship between self-control and self-regulated learning in students participating in Student Organizations; the correlation value of r is 0.689 at p = 0.000 (p < 0.01).